2017
DOI: 10.1063/1.4982933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reducible oxide–metal cluster charge transfer on the structure and reactivity of adsorbed Au and Pt atoms and clusters on anatase TiO2

Abstract: We carried out density functional theory calculations to study the influence of oxide-metal charge transfers on the structure, energetics, and reactivity of Au and Pt atoms, dimers, and trimers adsorbed on the (101) surface of reduced anatase TiO 2 . Pt clusters interact much more strongly with the TiO 2 support than Au clusters, and, with the exception of single Pt adatoms, generally behave as electron acceptors on reduced TiO 2 , whereas Au clusters can both accept and donate charge on the reduced surface. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 65 publications
(86 reference statements)
8
15
0
Order By: Relevance
“…Figure S6 displays the XRD patterns of the TiO 2 and NCDs/TiO 2 films. The dominant peaks in both samples are assigned to the (101) facet of the anatase phase, which is considered to be the most stable structure in anatase TiO 2 . The diffraction patterns of NCDs/TiO 2 are in good match with that of the TiO 2 , which contains mostly the anatase phase with small amount of rutile (JCPDS 01-084-1286 and 01-073-2224), indicating that the deposition of NCDs does not cause any obvious changes in TiO 2 crystallinity …”
Section: Results and Discussionmentioning
confidence: 83%
“…Figure S6 displays the XRD patterns of the TiO 2 and NCDs/TiO 2 films. The dominant peaks in both samples are assigned to the (101) facet of the anatase phase, which is considered to be the most stable structure in anatase TiO 2 . The diffraction patterns of NCDs/TiO 2 are in good match with that of the TiO 2 , which contains mostly the anatase phase with small amount of rutile (JCPDS 01-084-1286 and 01-073-2224), indicating that the deposition of NCDs does not cause any obvious changes in TiO 2 crystallinity …”
Section: Results and Discussionmentioning
confidence: 83%
“…However, a non-negligible fraction of the donated charge (18%) is located at titanium sites, modulating its electronwithdrawing power and implying a formal partial reduction of Ti(IV) in the neighborhood (d ≤ 3 Å) of the interface. On average, ⟨q Ti ⟩ of the most exposed Ti layer decreases from +2.000 (6) |e| in the isolated anatase slab to 1.968(2) |e| in the composite TiO 2 /Ag system. On the contrary, Ag atoms in close contact with the interfacial O surf atoms are neatly positive (Figure 1b, red triangles), 36 while the other ones are neutral or slightly negative (Figure 1b, green diamonds).…”
mentioning
confidence: 97%
“…Recently, Serpone et al suggested that such a third generation of photoactive devices has the potential to significantly impact everyday life. Suitably designed nanoheterojunctions enhance synergistic functionalities and allow one to obtain “brave new materials” with physicochemical properties that are not simply the addition of the precursors’ ones but are completely new, different, and unexpected. , However, research on such devices is most often dominated by trial and error procedures, while a deep atomistic understanding of the phenomena inside of the junction region driving appropriate design of the final device is missing.…”
mentioning
confidence: 99%
“…If accurate thermodynamics are a priority, however, PBE with a minimal amount of correction already suffices for many transition metal oxides. 7 , 57 60 …”
mentioning
confidence: 99%
“…In contrast, pristine CeO 2 slabs exhibit no U dependence. , Regardless, such trends are always a source of bias in redox reactions at any specific choice for U . If accurate thermodynamics are a priority, however, PBE with a minimal amount of correction already suffices for many transition metal oxides. , …”
mentioning
confidence: 99%